Assessment of the Internal Consistency of Two Polish References in Detecting Short Stature and Obesity in Children and Adolescents - Kułaga, Zbigniew; Kotowska, Aneta (Anthropological Review, 2025)
In paediatric practice, growth references are used by doctors and nurses to evaluate a child’s growth status. We present an assessment of the internal consistency of two Polish references in detecting short stature and obesity in children and adolescents. Key diagnostic thresholds, the 3rd percentile for height and the 95th for Body Mass Index (BMI), were selected for comparison. Percentiles were calculated for hypothetical heights 0.2 cm lower than the third percentile of specific references and 0.1 units lower than the 95th percentile of specific references, in the case of height and BMI references, respectively. The z-scores were calculated and converted to percentiles. MS Excel was used. Around the 3rd percentile of height and the 95th percentile of BMI, there is a discrepancy in the Warsaw growth reference for measured height and BMI, respectively, and the calculated percentile. In the case of the Polish 2010 and 2012 growth references, a hypothetical height 0.2 cm below the third percentile of height-for-age reference yielded percentiles below 3 for all ages in both sexes. The Polish 2010 and 2012 growth references for measurements 0.1 units below the obesity threshold yielded percentiles of 94.69–94.86 in boys and girls. The Polish 2010 and 2012 growth references provide consistent and coherent calculation results for the 3rd percentile of height and the 95th percentile of BMI for children and adolescents aged 3–18 years.